2014
DOI: 10.25100/cm.v45i3.1471
|View full text |Cite
|
Sign up to set email alerts
|

Practice of preventive dentistry for nursing staff in primary care

Abstract: Objectives: Determine the domain of preventive dentistry in nursing personnel assigned to a primary care unit. Methods: Prospective descriptive study, questionnaire validation, and prevalence study. In the first stage, the questionnaire for the practice of preventive dentistry (CPEP, for the term in Spanish) was validated; consistency and reliability were measured by Cronbach's alpha, Pearson's correlation, factor analysis with intra-class correlation coefficient (ICC). In the second stage, the domain in prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…One of these studies showed poor knowledge about preventive dentistry in primary care nursing. It also showed better knowledge among female nurses and better knowledge among public health nurses in respect to other categories [12]. One that was conducted on critical care nurses found that their oral health knowledge is inadequate which makes them unprepared for caring for the oral health of critically ill patients [11].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One of these studies showed poor knowledge about preventive dentistry in primary care nursing. It also showed better knowledge among female nurses and better knowledge among public health nurses in respect to other categories [12]. One that was conducted on critical care nurses found that their oral health knowledge is inadequate which makes them unprepared for caring for the oral health of critically ill patients [11].…”
Section: Discussionmentioning
confidence: 98%
“…Studies that used other questionnaires, not the HU-DBI, also demonstrated a lack of self-reported oral health knowledge among nurses [11][12][13]. One of these studies showed poor knowledge about preventive dentistry in primary care nursing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation